Experimental study and numerical simulation of uniaxial compression on artificial rock samples with Z-shaped fractures - Xiong, Liangxiao; Gong, Liyu; Zhou, Tao; Xu, Zhongyuan; Hu, Deye (Archives of Civil Engineering, 2026)
To study the influence of the inclination and length of Z-shaped fissures on the mechanical properties and failure characteristics of the rock mass, this study conducts a series of uniaxial compression tests on rock-like materials with prefabricated Z-shaped fractures. In addition, two-dimensional Particle Flow Code software is used to perform uniaxial compression numerical simulations. The results show that: (1) Other parameters are the same; under different gamma, beta has a significant impact on the variation trend of the compressive strength and elastic modulus of the specimen, showing an "M-shaped" pattern. (2) Under the same conditions, when beta ≠ 0 deg, the compressive strength and elastic modulus of the specimen are negatively correlated with gamma; however, when beta = 0 deg, both are positively correlated with gamma. (3) Under the same conditions, when gamma a ≠ 90 deg, the compressive strength and elastic modulus of the specimen show an "M-shaped" trend with increasing beta. However, when gamma_a = 90 deg, both are negatively correlated with beta. (4) Under the same conditions, for different beta, the compressive strength and elastic modulus of the specimen are positively correlated with gamma_a. (5) The main damage mode of Z-crack specimen is tensile shear damage.